Biochemical characteristics of aboveground phytomass of plant of the genus Astragalus L. in the right-bank of forest-steppe of Ukraine - Rakhmetov, Dzhamal; Bondarchuk, Oleksandr; Vergun, Olena; Fishchenko, Valentyna (ScienceRise: Biological Science, 2018)
Objective – to find out the specific features of the biochemical composition of the representatives of the Astragalus genus as valuable phyto-raw materials for medicinal and energy purposes in the conditions of the Right-Bank of Forest-Steppe of Ukraine. Materials and methods. The object of research is plants of the genus Astragalus species, in the collection fund of department cultural flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Phyto-raw materials were analyzed during the budding, flowering and fruiting phase in the biochemical laboratory of the department of cultural flora of the M.M. Gryshko National Botanical Garden of the NAS of Ukraine according to generally accepted methods. Processing of research results was performed by analysis of variance and statistical estimate of the average data using of program Microsoft Excel (2010). Results. The greatest amount of dry matter in all the investigated introducents accumulates in the fruiting phase (24,37–38,64 %) and the maximum value was in A. glycyphyllos. The total content of sugars significantly increases during the flowering phase. The highest was in A. glycyphyllos (20,00 %). Protein content in plants of the genus Astragalus in this period was 14,00–24,42 %, ascorbic acid respectively 102,44–398,45 %. A high level of ascorbic acid was released – A. ponticus. A high level of lipid content during the growing season (except for budding) was characterized by A. galegiformis. Intensive accumulation of cellulose in plants of the genus Astragalus is fixed in the flowering phase (34,84–42,36 %). The highest content of cellulose was characterized in plants A. falcatus. It was found that the most energy-producing plants were A. galegiformis and A. ponticus (more than 81 Gcal/ha), somewhat less valuable were A. falcatus plants (61–80 Gcal/ha). At an energy-productivity of 41–60 Gcal/ha, belong to the A. cicer and A. glycyphyllos plants. Conclusions. It was established that plants of the genus Astragalus species are characterized by a rich quantitative and qualitative composition of BAC in terms of dry matter. According to the biochemical composition, all accumulate sugars, vitamin C, carotene, lipids, protein, fiber and other valuable substances, which indicates the prospect of using them as valuable medicinal phytopreparations. The productivity of above-ground phytomass, the output of total energy and phyto-fuel per unit area gives grounds for considering data of introducts as valuable raw materials for the needs of bioenergy